2015
DOI: 10.1115/1.4031002
|View full text |Cite
|
Sign up to set email alerts
|

Annular Gap Bubble Column: Experimental Investigation and Computational Fluid Dynamics Modeling

Abstract: This paper investigates the countercurrent gas-liquid flow in an annular gap bubble column with a 0.24 m inner diameter by using experimental and numerical investigations. The two-phase flow is studied experimentally using flow visualizations, gas holdup measurements, and double fiber optical probes in the following range of operating conditions: superficial air velocities up to 0.23 m/s and superficial water velocities up to À0.11 m/s, corresponding to gas holdups up to 29%. The flow visualizations were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 69 publications
(91 reference statements)
1
35
1
Order By: Relevance
“…Extensive studies on the influence of the liquid velocity in the counter-current mode were performed by Besagni et al [28,34,46,[51][52][53][54], who found that the counter-current mode destabilized the homogeneous regime in all of the different configurations studied (viz. the pipe sparger in the annular gap and in the open tube configuration [34] and the spider sparger [46] [28,34,46,[51][52][53][54]. Recently, Trivedi et al [55] performed a detailed study on the hydrodynamics of counter-current bubble columns and found results in agreement with Besagni and co-authors.…”
Section: Gas Sparger Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive studies on the influence of the liquid velocity in the counter-current mode were performed by Besagni et al [28,34,46,[51][52][53][54], who found that the counter-current mode destabilized the homogeneous regime in all of the different configurations studied (viz. the pipe sparger in the annular gap and in the open tube configuration [34] and the spider sparger [46] [28,34,46,[51][52][53][54]. Recently, Trivedi et al [55] performed a detailed study on the hydrodynamics of counter-current bubble columns and found results in agreement with Besagni and co-authors.…”
Section: Gas Sparger Designmentioning
confidence: 99%
“…Similar trends were found by Otake et al [49], as already discussed when considering the flow regime transition. Besagni et al [34,46,[51][52][53][54] found that when increasing the liquid flowrate, a faster increase in the hold-up is observed at low U G , and the transition point also moves toward lower superficial gas velocities (Figures 16-18). This change was explained by the effect of the liquid flow, which slows down the rise of the bubbles, leading to higher hold-up-a more compact arrangement of bubbles leads to an earlier flow regime transition.…”
Section: Influence Of the Bubble Column Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Besagni, et al [83] experimentally investigated the influence of two inner pipes on counter-current flow in a bubble column, however this study is not directly relevant to the focus of this review paper due to the difference in geometry. The majority of the available experimental investigations of counter-current flows in vertical pipes focus on identifying the onset of flooding or counter-current flow limitation (CCFL).…”
Section: Counter-current Flow In Vertical Pipesmentioning
confidence: 99%